1985
DOI: 10.1093/nar/13.16.5771
|View full text |Cite
|
Sign up to set email alerts
|

Novel deletion mutants that enhance a distant upstream 5′ splice in the E3 transcription unit of adenovirus 2

Abstract: Region E3 of adenovirus is a "complex" transcription unit: i.e. different mRNAs and proteins arise by differential RNA 3' end selection and differential splicing of the primary transcript. We are using viable virus mutants to understand the controls that dictate the specificity and efficiency of the RNA processing signals. We describe a novel class of deletion mutations that enhance a natural 5' splice site located approximately 740 nucleotides (nt) upstream. In particular, deletions within nt 1691-2044 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 48 publications
3
19
0
Order By: Relevance
“…When analyzing various Ad2 mutants (dL762, dL712, ts1) that all carry intact Pb genes, we observed that trafficking of the Pb protein was never affected (Figure 2C). dL712 is an Ad2/Ad5 hybrid virus with a deletion of the E3 Ad death protein (ADP), (25,26), and the dL762 mutant has a deletion in the E3 14.7 K protein (27). Likewise, Ad2 ts1 bearing a point mutation in the L3/p23 protease gene which renders the protein incapable of packaging into newly synthesized virions at the restrictive temperature (28) clearly showed cell‐to‐cell spreading of its Pb protein.…”
Section: Resultsmentioning
confidence: 99%
“…When analyzing various Ad2 mutants (dL762, dL712, ts1) that all carry intact Pb genes, we observed that trafficking of the Pb protein was never affected (Figure 2C). dL712 is an Ad2/Ad5 hybrid virus with a deletion of the E3 Ad death protein (ADP), (25,26), and the dL762 mutant has a deletion in the E3 14.7 K protein (27). Likewise, Ad2 ts1 bearing a point mutation in the L3/p23 protease gene which renders the protein incapable of packaging into newly synthesized virions at the restrictive temperature (28) clearly showed cell‐to‐cell spreading of its Pb protein.…”
Section: Resultsmentioning
confidence: 99%
“…5). mRNAfis overproduced by dn712 (3,13) and dM763 (Brady et al, in preparation). It is probably also overproduced by d1764 because d1764 has nearly the same deletion as 14- Cys-labeled 10.4K from mRNA purified by hybridization from pm760-infected KB cells.…”
Section: Fig 5 Immunoprecipitation Of [35s]mentioning
confidence: 99%
“…A study by Deutscher et al (12) suggests a testable mechanism for alternative selection of Drosophila MHC exons that depends on selective repression of the 5' splice junction of the thorax-specific exon. They found that a 400-base region of the adenovirus E3 transcription unit represses use of a particular 5' splice site, perhaps by formation of an RNA stem-loop structure which prevents recognition of this splice site by the splicing machinery (55).…”
mentioning
confidence: 99%